The Use of Public Spaces in Traditional Residential Areas After Tourism-Oriented Renovation: A Case Study of Liu Xing Street in Yining, China - Dilidaner Dilixiati; Simon Bell (Land)
Public spaces in historical and cultural cities not only provide places for social interaction in people’s daily lives but also help visitors engage with local history and culture. Although extensive research has been conducted on the use of public spaces, little has been conducted on cities in developing countries, such as cities in Xinjiang, China. Therefore, this research selected a public space in a traditional Uyghur residential area in Yining, which is located in the northwest of Xinjiang, to investigate the current usage of public space in the context of the growing tourism industry. We employed behaviour mapping as the primary method for data collection and analysed it using ArcGIS. A total of 3052 data points were collected over a five-day observation period. We found that while a wide range of activities were observed at the study site, only a few took place with high frequency. The influence of the facilities at the study site on users’ behaviour is significant. In terms of spatial distribution, the number and diversity of activities also show a concentrated distribution in a certain sub-area. Therefore, the conclusions suggest that it is important to conduct post-use evaluations to investigate the attitudes and perceptions of local residents.